Studi Hubungan Struktur dan Aktivitas Senyawa Antioksidan dari Kulit Batang Kandis Gajah (Garcinia griffithii T. Anders) - ELFITA ELFITA; DACHRIYANUS DACHRIYANUS; SUPRIYATNA SUPRIYATNA; HUSEIN H. BAHTI (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
Four xanthones and two benzophenones from the stem bark of kandis gajah (Garcinia griffithii) by extraction and chromatographic methods have been isolated. The six compounds were determined as: 1,7-dihydroxyxanthone (1), 1,6,7-trihydroxyxanthone (2), 1,6-dihydroxy-3-methoxy-4,7-di-(3-methylbut-2-enyl)xanthone (3), 1,5-dihydroxy-3,6-di-methoxy-2,7-di-(-3-methylbut-2-enyl)xanthone (4), guttipherone I (5), and isoxanthochymol (6). All of the isolated compounds were submitted to antioxidant activity assay using three methods: (i) free radical scavenging method, (ii) xanthine-xanthine oxidase (XO) method, and (iii) nitroblue tetrazolium xanthine oxidase (NBT/ XO). Guttipherone I (5) and isoxanthochymol (6) have strong antioxidant activity (IC50 ≤10.2 µg/mL), 1,6,7-trihydroxyxanthone (2) and 1,6-dihydroxy-3-methoxy-4,7-di-(3-methylbut-2-enyl)xanthone (3) as active compounds (IC50 ≤ 100 µg/mL), while 1,7-dihydroxyxanthone (1) and 1,5-dihydroxy-3,6-dimethoxy-2,7-di-(3-methylbut-2-enyl)xanthone (4) were inactive (IC50 > 100 µg/mL). Base on the data, antioxidant activity of isolated compounds was inhuenced by dihydroxyl groups at ortho position, number of hydroxyl group, and hydroxyl group at para position to C carbonyl at heterocyclic.